Application of International Best Practice Guideline in Diabetic Ulcer Patients - Sukmana, Mayusef; Sianturi, Roni; Aminuddin, Muhammad (Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Background: Diabetic ulcer is one of the complications of Diabetes mellitus. Assessment of diabetic ulcers is done as a basis in determining wound care and therapy provided so that it needs to know its characteristics.Purpose: This study was to determine the characteristics of wounds assessment tools diabetic ulcer International Best Practice Guideline (IBPG).Method: The study design was descriptive with a case study approach, the sampling technique was purposive sampling carried out in May 2019 with three respondents. The instrument used is the wound assessment tool International Best Practice Guideline which contains: sensation, callus, wound base, temperature and location.Results: Respondents 1 experienced neuroiskemic injuries. Respondent 2 suffered neuropathic injuries and Respondent 3 had ischemic injury.Conclusion: Characteristics of ulcers based on the International Best Practice Guidelines respectively, neuroiskemic, neuropathic and ischemic ulcers. Health workers are expected to apply a more detailed assessment of diabetic ulcers so that they can determine the appropriate treatment.